2010
DOI: 10.1185/03007995.2010.493788
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adherence among Alzheimer's disease patients receiving oral therapy

Abstract: Among the several variables assessed, being male, >or=86 years of age, having a greater overall daily pill burden, or using a lower formulary tier AD medication was associated with better adherence to oral AD medication in patients diagnosed with AD. The database had no information on caregiver support, medication management interventions, or use of adherence aids that may have affected adherence in this cohort, yet, a substantial proportion of patients (42%) remained non-adherent. A better understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
3
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 38 publications
0
68
3
2
Order By: Relevance
“…62,64 In the study by Amuah et al, 44 patients with AD paying for a greater proportion of their total prescription costs were significantly more likely to discontinue ChEI therapy. Studies of other drug classes have shown strong associations between worse adherence and (or) persistence and financial barriers in older, vulnerable patient groups.…”
Section: Patient-level Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…62,64 In the study by Amuah et al, 44 patients with AD paying for a greater proportion of their total prescription costs were significantly more likely to discontinue ChEI therapy. Studies of other drug classes have shown strong associations between worse adherence and (or) persistence and financial barriers in older, vulnerable patient groups.…”
Section: Patient-level Factorsmentioning
confidence: 99%
“…44,50 This seemingly paradoxical finding may reflect an opportunity for more interactions with prescribers, with enhanced continuity of care leading to improved treatment persistence. Two other studies from the Netherlands 43 and the United States 62 reported lower persistence and adherence to ChEI therapy among patients with greater comorbidity. While a higher pill burden (that is, number of pills, tablets, or capsules taken on a regular basis) appeared to be unrelated to ChEI persistence, there may be a positive association between the number of medications and greater adherence to dementia pharmacotherapy.…”
Section: Patient-level Factorsmentioning
confidence: 99%
See 3 more Smart Citations